ICT integration in classrooms: The educators’ perspective based on their school and home ict use / Johan @ Eddy Luaran, Ahmad Danial Mohd Ghazali and Jasmine Jain - Luaran, Johan @ Eddy; Mohd Ghazali, Ahmad Danial; Jain, Jasmine (Universiti Teknologi MARA Pulau Pinang, 2014)
The development of Information and Communication Technology (ICT) influences much of our culture and lifestyle. The application of technology in teaching and learning gives a new paradigm in teacher’s teaching techniques. Previous studies have proven that the application of ICT has been able to revolutionize teachers' teaching techniques and pupils’ learning method. Therefore, this study was conducted to a selected number of secondary school teachers to investigate their utilization and ICT integration into classrooms. The nature of this study is quantitative, where questionnaires were utilized to collect data from 54 teachers. This study aimed to find out the availability of ICT equipment to the teachers both at home and school. Besides that, teachers’ ICT usage and their attitude towards ICT integration for teaching and learning were probed. The main finding of this study is despite the availability of ICT equipment in schools, these facilities has been underutilized by the teachers. In regard to teachers’ attitude towards ICT integration in their classrooms, results showed that the teachers highly acknowledged the importance of ICT, enabling more interesting lessons. In general, this study revealed fairly similar perceptions about the usage of ICT issues in secondary schools as raised in this paper. It is hoped that this study provides insights on ICT issues and motivate teachers to integrate ICT into their teachings in fostering students’ overall development.